Two new species (Polychaeta: Fauveliopsidae and Nerillidae) and other polychaetes from the marine lagoon cave of Jameos del Agua, Lanzarote (Canary Islands) - Núñez, J.; Ocaña, O.; Brito, M.C (Bulletin of Marine Science, 1997)
Nine species of polychaetes were collected from Jameos del Agua, Lanzarote, in shallow waters of a semi illuminated lagoon. Two new species are described: Fauveliopsis jameoaquensis Núñez, and Mesonerilla diatomeophaga Núñez. F. jameoaquensis is distinguished from the other species of the genus by having only 10 setigers. M. diatomeophaga is related to M. prospera Sterrer and Iliffe, 1982 from inland marine caves of Bermuda. M. diatomeophaga inhabits a carpet of diatoms on which it also feeds. A species of Macrochaeta, identified only to the generic level, is described, unfortunately only one incomplete specimen was collected.
World Polychaeta Database (WPolyDb)